Can hyperbaric oxygen be used to prevent deep infections in neuro-muscular scoliosis surgery? - (:unkn) unknown (BIOMED CENTRAL LTD, 2014)
Background: The prevalence of postoperative wound infection in patients with neuromuscular scoliosis surgery is significantly higher than that in patients with other spinal surgery. Hyperbaric oxygen has been used as a supplement to treat postsurgical infections. Our aim was to determine beneficiary effects of hyperbaric oxygen treatment in terms of prevention of postoperative deep infection in this specific group of patients in a retrospective study. Methods: Forty two neuromuscular scoliosis cases, operated between 2006-2011 were retrospectively reviewed. Patients who had presence of scoliosis and/or kyphosis in addition to cerebral palsy or myelomeningocele, postoperative follow-up >1 year and posterior only surgery were the subjects of this study. Eighteen patients formed the Hyperbaric oxygen prophylaxis (P-HBO) group and 24, the control group. The P-HBO group received 30 sessions of HBO and standard antibiotic prophylaxis postoperative, and the control group (received standard antibiotic prophylaxis). Results: In the P-HBO group of 18 patients, the etiology was cerebral palsy in 13 and myelomeningocele in 5 cases with a mean age of 16.7 (11-27 yrs). The average follow-up was 20.4 months (12-36mo). The etiology of patients in the control group was cerebral palsy in 17, and myelomeningocele in 7 cases. The average age was 15.3 years (8-32 yrs). The average follow-up was 38.7 months (18-66mo). The overall incidence of infection in the whole study group was 11.9% (5/42). The infection rate in the P-HBO and the control group were 5.5% (1/18), and 16.6% (4/24) respectively. The use of HBO was found to significantly decrease the incidence of postoperative infections in neuromuscular scoliosis patients. Conclusion: In this study we found that hyperbaric oxygen has a possibility to reduce the rate of post-surgical deep infections in complex spine deformity in high risk neuromuscular patients.
Keywords: Neuromuscular scoliosis; Infection; Treatment; Hyperbaric oxygen; RISK-FACTORS; PEDIATRIC SCOLIOSIS; TREATMENT-OUTCOMES; WOUND INFECTIONS; THERAPY; MANAGEMENT; INJURIES; FUSION